2021
DOI: 10.1002/ar.24699
|View full text |Cite
|
Sign up to set email alerts
|

Genital anatomy and copulatory interactions in the broad snouted Caiman (Caiman latirostris)

Abstract: The broad snouted caiman is a crocodylian native to South America that is subject to extensive conservation management in both wild and farming environments. Although reproductive behaviors like egg laying and clutch care have been examined in this species, little else is known about their copulatory system. We examined the anatomy of male and female cloacal and genital tissues ex vivo to build hypotheses of their interactions during copulation and the effects of that interaction on insemination. Male phallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…7,[10][11][12] Copulatory locks are well recognized in canids [13][14][15] and involve the intravaginal swelling of the bulbus glandis during copulation. 16 Other mammals exhibit copulatory locks including the shrew, 17 primates 18 and potentially caiman species, 19 but different mechanisms have been proposed including the presence of penile spines and the shape of the penis. 20 Copulatory lock behavior is common in rodents, and has been described in the spiny mouse (Acomys cahirinus), the hopping mouse (Notomys alexis), 21 the southern and northern grasshopper mouse (Onychomys torridus, O. leucogaster), 22 white-throated wood rats (Neotoma albigula), golden mouse (Ochrotomys nuttalli), 23 and northern pygmy mouse (Baiomys taylori).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[10][11][12] Copulatory locks are well recognized in canids [13][14][15] and involve the intravaginal swelling of the bulbus glandis during copulation. 16 Other mammals exhibit copulatory locks including the shrew, 17 primates 18 and potentially caiman species, 19 but different mechanisms have been proposed including the presence of penile spines and the shape of the penis. 20 Copulatory lock behavior is common in rodents, and has been described in the spiny mouse (Acomys cahirinus), the hopping mouse (Notomys alexis), 21 the southern and northern grasshopper mouse (Onychomys torridus, O. leucogaster), 22 white-throated wood rats (Neotoma albigula), golden mouse (Ochrotomys nuttalli), 23 and northern pygmy mouse (Baiomys taylori).…”
Section: Discussionmentioning
confidence: 99%
“…Neither mouse had a clinical history before presentation and were housed as a breeding trio with another female in an individually ventilated cage (no. 19, Thoren Caging Systems, Inc., Hazelton, PA, USA), provided with a natural ingredient, closed source, flash-autoclaved, c-irradiated feed (PicoLab V R Rodent Diet 20 [5053] chow diet, Lab-Diet Co., St. Louis, MO, USA) and autoclaved acidified reverse osmosis purified water (pH 2.5-2.8 with hydrochloric acid) ad libitum and bulk autoclaved aspen chip bedding (PWI Industries, Quebec, Canada). 1 Each cage was provided with a Glatfelter paper bag containing 6 g of crinkled paper strips (EnviroPak V R , WF Fisher and Son, Branchburg, NJ, USA) for enrichment.…”
Section: Case Reportmentioning
confidence: 99%
“…Historically overlooked due to difficulties in collection and imaging of soft tissue (Orbach, 2022 ), modern techniques (including silicone casting, computed tomography and magnetic resonance imaging) offer the opportunity for shape complexity analysis at the same standard as those techniques used here (Clear et al, 2022 ). A comprehensive understanding of both male and female genital anatomy, covariance of genital morphology (André et al, 2020 ) and analysis of copulatory fit, as conducted in other species (cetaceans: Orbach et al, 2017 ; caiman: Moore et al, 2021 ), will provide the opportunity to explore how variation in form might influence copulatory function in Musteloidea.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this smooth‐muscle structure plays roles in ventilation and possibly buoyancy control. Moore et al (2022) use MRI, 3D modeling and other approaches to study the morphology of the genitals of Caiman latirostris and how they work in copulo . They found the male glans was capable of forming a genital lock during copulation, but also that the coiled, muscular walls of the vagina is likely capable of excluding semen, perhaps being yet another a mechanism of sexual selection.…”
Section: Figurementioning
confidence: 99%